2002
DOI: 10.1364/ao.41.000096
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-multiplexed diffractive optical elements fabricated by subwavelength structures

Abstract: Polarization-multiplexed phase-only diffractive optical elements with subwavelength structures are proposed and fabricated. The differences among the phase modulations result from the differences among the effective indices exhibited in the subwavelength structures with various filling factors and surface profiles, and the phase retardations are obtained by the relief depth of the structures. The polarization-selective property is achieved by the polarization dependence of the effective indices exhibited in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Rotating the device to make its TE axe have 45Û with respect to the polarizer axe and then measuring the intensities from the analyzer T TE and T TM , when its axe was parallel and perpendicular to that of the polarizer. The phase difference /3 resulted in the quarter-wave plate can be calculated from following equation TM TE TM TE I I T T )/ ( − = δϕ cos (5) The result from Eq. 5 was 86Û for the fabricated element.…”
Section: Synthesis and Fabrication Of Wave Plates With The Multi-layementioning
confidence: 99%
See 1 more Smart Citation
“…Rotating the device to make its TE axe have 45Û with respect to the polarizer axe and then measuring the intensities from the analyzer T TE and T TM , when its axe was parallel and perpendicular to that of the polarizer. The phase difference /3 resulted in the quarter-wave plate can be calculated from following equation TM TE TM TE I I T T )/ ( − = δϕ cos (5) The result from Eq. 5 was 86Û for the fabricated element.…”
Section: Synthesis and Fabrication Of Wave Plates With The Multi-layementioning
confidence: 99%
“…Zeitner et al [4] demonstrated and fabricated a polarization-selective amplitude computer generated hologram based on the polarization-dependent transmission characteristics of metal-stripe SWSs. Yu et al [5] proposed a depth-independent phase-only polarization-sensitive computer generated hologram by introducing the polarizationdependent and independent form-birefringent SWSs to construct the corresponding pixels. The methods proposed in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their optically active properties, polarization holographic gratings are promising in the production of high-function optical devices such as lights modulators, valves, polarization multiplexers and demultiplexers, polarized radiation splitters (Bunning et al, 2000;Cipparrone et al, 2000;Cipparrone et al, 2001a;Habraken et al, 1995;Ono et al, 2005;Wu et al, 2001;Yu et al, 2002). Such gratings are recorded on polarization-sensitive materials: photo-refractive crystals (Sturman et al, 1996), «guest-host» systems (Khoo, 1991;Slussarenko et al, 1997;Nikolova & Todorov, 1984), azopolymers (Naydenova et al, 1998;Labarthet & Rochon, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The effective refractive index eff n depends on polarization and is given in following form by the second-order approximation [11][12][13]: …”
Section: Introductionmentioning
confidence: 99%